2011
DOI: 10.1007/s11064-011-0651-7
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Oxidative Stress and Inflammatory Mediators in the Protective Effects of the Early Preconditioning Window Against Transient Global Ischemia in Rats

Abstract: Ischemic preconditioning (IPC), comprising exposure to sub-lethal short term ischemic events, has been shown to exert adaptive responses in many organs including the brain, thus guarding against exacerbations of ischemia reperfusion (IR). However, the mechanisms involved in the early phase of such a protection remain elusive; hence, the present study aimed to investigate the modulatory effect of preconditioning against IR induced injury on infarct size, free radicals, inflammatory/anti-inflammatory markers, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
(58 reference statements)
1
7
0
Order By: Relevance
“…Our results also show that apoptosis occurs to the same extent in all treatments. This could agree with previously published results indicating that caspase‐3 is not involved in the ischaemic preconditioning‐induced neuroprotection nor in the toxicity induced by ischaemia–reperfusion (Nassar et al 2012).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results also show that apoptosis occurs to the same extent in all treatments. This could agree with previously published results indicating that caspase‐3 is not involved in the ischaemic preconditioning‐induced neuroprotection nor in the toxicity induced by ischaemia–reperfusion (Nassar et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…In our model, hypothermia induced a moderate level of lipid peroxidation, but when hypothermia was induced prior to an acute episode of hypoxia the oxidative stress indicators and necrosis were both attenuated. It has previously been demonstrated that during the early phase of ischaemic preconditioning, ROS and NO production afford protection against further damage in cerebral ischaemia (Schaller & Graf, 2002; Nassar et al 2012) and in ischaemia of cardiomyocytes (Lebuffe et al 2003). The decrease in the generation of free radicals has been also described in hippocampal cultures at 31°C during deprivation of oxygen and glucose (McManus et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As referred to hypothermia, our results [33] and others [7780] lead us to propose the hypothesis that hypothermia through the generation of RONS and increasing GSH can induce protective mechanisms. The most remarkable of hypothermia is that protection is observed both when induced prior to injury, as a preconditioning model (experimental hypothermia), and when applied after damage (therapeutic hypothermia).…”
Section: The Role Of Rons As Signaling Moleculesmentioning
confidence: 61%
“…The mechanisms of signaling pathways in cardiac ischemic preconditioning have been recently reviewed [75] and it is believed that RONS play an important role in the mechanisms of preconditioning and protection. During the early phase of preconditioning ROS and NO production afford protection against further damage in cerebral ischemia [79, 80] and in cardiomyocytes ischemia [81]. The production of adenosine during ischemic preconditioning could mediate the protective effects [82].…”
Section: The Role Of Rons As Signaling Moleculesmentioning
confidence: 99%
“…Sevoflurane-induced postconditioning of global cerebral ischemia in adult rats is associated with suppression of pro-inflammatory cytokines and increased IL-10 [40]. Similarly, global cerebral ischemia in adult rats was associated with increased pro-inflammatory cytokines and decreased IL-10, which was reversed by mild ischemic preconditioning [41]. Thus, it is possible that the combination of greater cortisol and anti-inflammatory cytokines may have contributed in part to the decreased microglial and astrocyte activation seen with the combination of LPS and asphyxia compared to either LPS or asphyxia alone.…”
Section: Discussionmentioning
confidence: 99%